Meningkatkan Motivasi Belajar dengan Media Audio Visual pada Pembelajaran Senam Aerobik Siswa Kelas X1 IPA di SMAN 1 Rengasdengklok - Mumtaz Arifin; Saepul Ma’mun; Ardawi Sumarno (Jurnal Ilmiah Wahana Pendidikan, 2021)
The purpose of this study was to determine the level of student motivation to learn aerobic exercise through audiovisual media. The method used in this research is experimental research. The total respondents who participated were 89 students of class XI IPA SMAN 1 Rengasdengklok who were taken using proportional random sampling technique. The research design used a pretest-posttest control group design. The instrument used is a research questionnaire (learning motivation and perception of audio-visual media), Cooper test. and aerobic exercise. The results of this study are the average learning motivation of the experimental class increased by 10.98% while the control class only increased by 6.25%. The average perception of audio-visual media in the experimental class increased by 7.03% while the control class only increased by 3.04%. The average Cooper test in the experimental class increased by 11% while the control class only increased by 0.29%. The average result of the experimental class aerobic exercise increased by 6.35% while the control class only increased by 5.21%. The conclusion of this research is that there are differences in learning motivation, perception of audio-visual media, cooper test, and aerobic exercise learning outcomes between the experimental class and the control class.